The construct and predictive validity testing of Indonesian entrepreneurial competence inventory-situational judgment test model - Benedicta Prihatin Dwi Riyanti; Angela Oktavia Suryani; Christine Winstinindah Sandroto; Silverius Y. Soeharso (Journal of Innovation and Entrepreneurship, 2022)
This research aimed to test the internal and external validity of the Indonesian Entrepreneurial Competence Inventory constructed based on the situational judgment test (SJT) model. Spencer's entrepreneurial competence theory and interviews with entrepreneurs were employed to build the items. The internal construct validity was tested by applying confirmatory factor analysis (CFA). In contrast, the external construct validity was tested by implementing correlations with other tests that were theoretically correlated with entrepreneurial competency, namely, the previous entrepreneurial competence (Likert-scale model) and risk behavior. The predictive validity was analyzed using correlation testing with an instrument assessing balanced scorecard measurement of entrepreneurial achievement. A sample of 149 entrepreneurs from industrial cities in Indonesia was recruited via convenience sampling. The CFA analyses showed that nine dimensions of the Indonesian Entrepreneurial Competencies Inventory were valid. In the correlation testing with risk-taking behavior and business success, all dimensions were significantly valid, except the see and act on opportunity dimension. However, in the correlation with the previous entrepreneurial competence scale, a significant correlation was found only with a commitment to work. In further analysis, the correlation between dimensions of the current inventory and dimensions of the previous scale showed significant correlations between the competence of seeing opportunity and commitment to work, assertiveness, and persuasion. The impact to the future research and practice application were discussed.
Keywords: 650; Confirmatory factor analysis; Construct validity; Indonesian entrepreneurial competence inventory; Predictive validity; Situational judgment test